Feed grain micronising plant - Kipriyanov Fedor; Savinykh Petr (E3S Web of Conferences, 2023)
The heating process of micronisation plays a paramount role in reducing the amount of anti-pittaels in the feed grain, changing the grain structure and increasing the availability of nutrients and improving their digestibility. The efficiency of heating generally depends on the design solutions used in the micronizing plant. This article gives an overview of some designs of installations for forage grain micronisation and presents the design of an installation for infrared micronisation of forage grain, which makes it possible to increase the efficiency of treatment, by reducing the burning of grain to the surface and ensuring uniformity of treatment.